The role of psychosocial intervention on the course of the disease in persons with severe mental disorders - A. Popova-Varbanova; V. Getova (Trakia Journal of Sciences)
The study includes 220 people with severe mental disorders, men and women, of ages 18-70, placed for compulsory treatment in psychiatric institutions in the area of Sofia city and Sofia region. The patients were hospitalized for the period from January 2013 to December 2015. Social factors, such as age, family status and support were taken into account. The patients’ usages of the service of psychosocial rehabilitation, as well as subsequent hospitalizations, were monitored for one year.